Evaluasi Kebijakan Distribusi Pupuk Bersubsidi di Kabupaten Gresik - Ninin Adeliya Citra; M. Kendry Widiyanto; Anggraeny Puspaningtyas (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Gresik district is experiencing problems with subsidized fertilizer from the government. The scarcity of fertilizer in Gresik district is not only caused by a lack of fertilizer availability, but can also be caused by delays in distribution. Finally, there is a risk of excessive fertilizer use. The purpose of this study is to determine the availability and needs of subsidized fertilizers, evaluate the implementation of fertilizer distribution, and provide recommendations for developing effective and efficient fertilizer distribution in Gresik Regency. This research uses a qualitative method. This research refers to the evaluation theory according to William N Dunn which consists of 6 indicators, namely effectiveness, efficiency, adequacy, equity, responsiveness and permanence. The result of this research is that the distribution of subsidized fertilizers has been effective, but there are still a few obstacles to scanning ID cards for the T-PUBRES application. Based on data from the Gresik Regency Agriculture Office, there is no shortage of subsidized fertilizer in Gresik Regency, but indeed the Gresik Regency subsidized fertilizer allocation from the Ministry of Agriculture is only part of the e-allocation. The delivery of subsidized fertilizer to kiosks is also good where the distribution is also in accordance with the policy. The implication of this research is that the Gresik Regency Agriculture Office needs to collaborate with the Gresik Regency Population and Civil Registry Office to improve the KTP of farmers so that it can be read by the REKAN KIOS application to make it easier for farmers to get subsidized fertilizer.